Automated multi-agent negotiation framework for the construction domain - Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M.; Idrus A. (Springer Verlag, 2023)
Artificial intelligence; Automation; Autonomous agents; Decision making; Multi agent systems; Software agents; Automated negotiations; Conflict resolution algorithms; Decision making process; Intelligent software agent; Multiagent negotiation; Negotiation algorithm; Proposed architectures; Value management; Intelligent agents